Triggering Receptors Expressed on Myeloid Cells 1 : Our New Partner in Human Oncology? - Muller, Marie; Haghnejad, Vincent; Lopez, Anthony; Tiotiu, Angelica; Renaud, Stéphane; Derive, Marc; Bronowicki, Jean-Pierre (Frontiers in Oncology, 2022)
Inflammation is recognized as one of the hallmarks of cancer. Indeed, strong evidence indicate that chronic inflammation plays a major role in oncogenesis, promoting genome instability, epigenetic alterations, proliferation and dissemination of cancer cells. Mononuclear phagocytes (MPs) have been identified as key contributors of the inflammatory infiltrate in several solid human neoplasia, promoting angiogenesis and cancer progression. One of the most described amplifiers of MPs pro-inflammatory innate immune response is the triggering receptors expressed on myeloid cells 1 (TREM-1). Growing evidence suggests TREM-1 involvement in oncogenesis through cancer related inflammation and the surrounding tumor microenvironment. In human oncology, high levels of TREM-1 and/or its soluble form have been associated with poorer survival data in several solid malignancies, especially in hepatocellular carcinoma and lung cancer. TREM-1 should be considered as a potential biomarker in human oncology and could be used as a new therapeutic target of interest in human oncology (TREM-1 inhibitors, TREM-1 agonists). More clinical studies or clinical trials are urgently needed to confirm TREM-1 (and TREM family) roles in the prognosis and the treatment of human solid cancers.